Faktor-Faktor Yang Mempengaruhi Kepuasan Kerja Bidan Dan Implikasinya Terhadap Kinerja Bidan di DKI Jakarta - Euis Saadah (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2015)
The purpose of this study was to obtain empirical evidence and conclusions regarding the factors affecting nurse job satisfaction which implicatedto the nurse performance in jakarta. Methods of data analysis which used to test the hypothesis was path analysis. The independent variable of the study are: the characteristics of nurse (X1), workplace (X2), enabling environments (X3), and access to information (X4), and the dependent variable is nurse job satisfaction(Y). The results of this study show that: (1) there is a significant effect, either partially or simultaneously from nurse characteristics, work environment, enabling environments, and access to information on nurse job satisfaction in Jakarta, with the amount of influence by 75.59 percent , (2) there is a significant effect of job satisfaction on nurse performance in Jakarta, with the amount of influence at 79.03 percent.